Meningkatkan Kemampuan Bermain Gitar Pada Mata Pelajaran SBdP Dengan Menggunakan Metode Latihan Terbimbing Pada Siswa Kelas V Di SDN 3 Tentena - Tanggerahi, Lawrence; Lagandesa, Yun Ratna; Kadek Hariana; Lapasere, Sisriawan (JURNAL DIKDAS, 2023)
This study aims to improve the ability to play guitar in SBdP class V SDN 3 Tentena. The population in this study were all fifth grade students in the 2023/2024 school year, totaling 24 students. Data collection techniques using observation, interview and documentation techniques. Based on the results of research on the use of guided practice methods to improve the ability to play guitar in SBdP subjects in class V SDN 3 Tentena, it can be concluded that there was an increase in the ability to play guitar in students from cycle I to cycle II. The increase can be seen in cycle I the number of students who developed very well was only 3 people with a frequency of 12.5%, increasing in cycle II to 7 people with a frequency of 29.16%. This shows the number of students who developed very well increased by 4 people with a frequency of 16.66%, students who developed as expected in cycle I there were 2 people with a frequency of 8.33% increased in cycle II to 13 people with a frequency of 54.16%. This shows that students who developed as expected increased by 11 people with a frequency of 45.83% from cycle I to cycle II.